(3GdeONd Edi GdEOGQI GdeGdjI GdMOjKI (B:s (3GdJMdjd GdeGdj h GbJUGOjGJ GdGSJKeGQ h GdJehjd (B/s - (3Ydj, Mfajs ((3GdbGgQI(B: s (3OGQ GdcJGH GdMOjK(B, s, 2008)
(3jVe GdJMdjd GdeGdj hGJNGPGJ GdbQGQGJ, GdJMdjd GdeGdj, GdJNWjW GdeGdj hGdQbGHI, GdESJKeGQGJ GdQCSeGdjI, GdEJaGb GdQCSeGdj, CSGdjH Jbjje GdEbJQGMGJ GdESJKeGQjI aj XQha GdKHGJ hGdJCcO, JcdaI GdCehGd hGJNGP bQGQGJ GdESJKeGQ, GdJehjd GdNGQLj hGdOGNdj hefgL bjGS JcdaJg, GdJcdaI GdeQLMI ddCehGd cefgL ddJbjje hGdeaGVdI deTQhYGJ GdESJKeGQ, GdESJKeGQGJ GdEMdGdjI, GdJehjd GdbUjQ GdCLds
Keywords: (3GdEOGQI GdeGdjIs; (3GdESJKeGQs; (3GdJehjds